Direct Surfactant-Impregnated Activated Carbon for Adsorption of Reactive Blue 4 - S.W, Puasa; K.N, Ismail; N.A.I., Khairi (International Journal of Engineering and Technology, 2018)
The present investigation deals with the enhanced of adsorptive removal of Reactive Blue 4 (RB4) from an aqueous solution using Surfactant-impregnated Activated Carbon (SIAC). The study on direct impregnation method was investigated using palm-based esterquat (PBE) surfactant. The effects of surfactant concentration, temperature and pH on dye removal were discussed to determine the efficiency of adsorption process. Results obtained from this study shows that the best RB4 dye removal obtained was 67.25% at PBE concentration of 128 mg/L in 5 hours contact time and operating temperature of 50â°C. It was observed that adsorption of RB4 dye was enhanced by modification of AC with cleavable cationic surfactant via direct impregnation method. The selected data obtained was fitted using multilinear regression via Excel Software. The regression analysis shows that the R2 and adjusted R2 obtained were 0.973 and 0.905, respectively. The ANOVA analysis proved that the mathematical expression can be used to predict the adsorptive removal of RB4 dye from an aqueous solution.Â Â